PEMBERDAYAAN KELUARGA DALAM MENINGKATKAN PENGETAHUAN DAN KETERAMPILAN PENDERITA DIABETES MELLITUS DALAM DETEKSI DINI DIABETIC FOOT ULCER - Sentana, Aan Dwi; Cembun; Moh. Hasbi (Poltekkes Kemenkes Mataram, 2025)
Identifying diabetic patients with sensory disturbances that ultimately lead to diabetic foot ulcers (DFU) is very important. The data on Diabetes Mellitus patients in Batu Kumbung village in 2023 shows a total of 57 patients. Based on the results of a preliminary study with 25 diabetes patients, it was found that 20 individuals (80%) reported symptoms of neuropathy, specifically tingling sensations in their feet, while 5 individuals (20%) did not complain of any tingling in their feet. Meanwhile, the knowledge and skills of the families of patients suffering from diabetes in detecting diabetic foot ulcers (DFU) early were all (100%) found to be lacking.The results showed a change in the knowledge of the families of patients in performing early detection of Diabetic Foot Ulcers, with those having insufficient knowledge decreasing from 15 individuals (75%) to having good knowledge increasing to 18 individuals (90%). The skills of families in performing early detection of Diabetic Foot Ulcers improved from insufficient skills in 20 individuals (10%) to good knowledge in 18 individuals (90%). For the foot health condition, the examination results showed that only 2 out of 10 people were at risk. After health condition training, none of the 20 diabetes patients experienced the risk of DFU (100%). Meanwhile, regarding blood sugar levels, out of 10 people, 5 (50%) had abnormal blood sugar levels, which increased to 15 people (75%) with normal blood sugar levels, leaving only 5 (25%) with abnormal blood sugar levels.Therefore, the role of the family is needed in monitoring health conditions, especially foot health, so that wounds in diabetes patients can be prevented.